Working with language learner histories from three perspectives: Teachers, learners and researchers - Mercer, Sarah (Studies in Second Language Learning and Teaching, 2013)
Recent developments in SLA, such as learner-centredness, social constructivism, the postmethod era, and complexity perspectives, have highlighted the need for more localized, situated understandings of teaching and learning and greater recognition of learner individuality and diversity. In this article, I suggest an effective way of meeting these needs is to employ learner histories. This powerful form of writing allows learners to use their L2 to engage in authentic, personally meaningful communication with others about their identities, experiences, perceptions and emotions related to their language learning histories. As a text type, they are able to facilitate a more holistic perspective of the learner’s life and reveal the unique interconnections that an individual makes across various domains. They also enable the situated, contextualised and dynamic nature of their learning experiences to become apparent and provide learners with a genuine, motivating purpose for writing. Exploring data generated in Austria with tertiary-level EFL learners, I seek to illustrate some of the rich potential of these text types from three perspectives, namely, those of the teacher, learner and researcher.